PERBANDINGAN PEMBINAAN KOMPETENSI PROFESIONAL GURU OLEH KEPALA SEKOLAH SD DENGAN MIN - Usman Usman (UNIVERSITAS BENGKULU, 2015)
The purpose of this study is to describe the ratio of professional development of teachers by principals between SD Negeri 16 Seluma with MIN Bungamas Seluma on aspects : mastering the material , managing learning programs , manage the classroom , using the media , mastering the educational foundation , manages the interaction of learning , and assess achievements students . The method used is descriptive evaluative . Results of the study is the result of development of professional competence of teachers in primary schools 16 SelumaSeluma compared with the guidance in the MIN Bungamas Seluma Seluma almost the same , only the existing infrastructure in the district Seluma MIN Bungamas still inadequate , so the coaching is done by the head less school goes well .Keywords : comparison , professional competence , teachers, principals